Corn protein hydrolysate as a novel nano-vehicle: Enhanced physicochemical stability and in vitro bioaccessibility of vitamin D3. (October 2016) - Lin, Yuan; Wang, Yong-Hui; Yang, Xiao-Quan; Guo, Jian; Wang, Jin-Mei
Abstract: The application of colloidal delivery systems for the encapsulation, protection and increased bioavailability of bioactive ingredients has recently gained increasing interest. The aim of this work was to prepare corn protein hydrolysate-based vitamin D3 (CPH-VD3 ) nanocomplexes. UV and FT-IR spectra indicated the existence of non-covalent interactions (i.e. hydrogen bonding) between CPH and VD3 . The result from X-ray diffraction further suggested the formation of amorphous structure of VD3 after its complexation with CPH. Additionally, dynamic light scattering and transmission electron microscope showed that the CPH-VD3 complexes exhibited a spherical structure with a size scale from 102 to 121 nm. The encapsulation and loading efficiency of VD3 could reach 97% and 9%, respectively. Furthermore, the complexation obviously avoided spontaneous particle aggregation of VD3 against ionic strength ([NaCl] ≤ 200 mmol/L). The remaining ratio of the encapsulated VD3 after exposure to high levels of UV light was as high as 72%. More importantly, in vitro bioaccessibility of VD3 could be up to 95% for the complexes. This study demonstrated that CPH could serve as a novel nano-vehicle for VD3 and it opens up the possibility of using CPH to construct the colloidal delivery system. Highlights: Corn protein hydrolysate based VD3 nanocomplex was successfully constructed. The complexes showed good colloidal stability against ionic strength. Corn protein hydrolysate could protect VD3 from the damaging effect of UV light. The bioaccessibility of VD3 in the complexes was significantly enhanced.